PERSISTENT ELECTRICAL ANOMALIES PRODUCED BY FRACTURE OF ROCKS - Balbachan M.Y. (My University, 1988)
We investigated the total charge of rock blocks that have required long-term polarization by failure or friction, and thus the exchange of charge between such blocks and the surroundings. With a view to the geophysical applications of this research, we also made sure that the experimental conditions simulate the natural conditions for generating the electret state. The results suggest that positively charged regions may be generated in earthquake preparation zones. Observing the development of such regions by means of regular topographic surveys is a possible way of predicting crustal earthquakes. The proposed model does not contradict current data on electrical and hydrogeochemical earthquake precursors.